Quels modes de voyage du modèle d’écoquartier périurbain ? Une comparaison des modalités de circulation classique et numérique de deux opérations franciliennes - Claire Doussard; Claire Fonticelli (Développement Durable et Territoires)
This article examines and compares the mobility conditions associated with the management of two « experimental » and « exemplary peri-urban eco-neighborhoods in the Île-de-France region, the eco-neighborhood of Le Presbytère in Bouray-sur-Juine, and the eco-hamlet of Champ Foulon in Saint-Cyr-en-Arthies. It explores more specifically the travel modes associated with different stakeholders and the State, impacting the circulation of the peri-urban eco-neighborhood model, according to two approaches. The first is based on classic mobility modalities, associated with the meetings of planning professionals and inhabitants. The second relates to the circulation of information on the internet. The different analyses reveal that if the State and the Regional Natural Parks are figures of authority when it comes to the circulation of the peri-urban eco-neighborhood model, the important input of the Champ Foulon inhabitants contributes significantly to the circulation of information on this neighborhood development, more specifically on the Internet.